دراسة تأثير المستخلص الكحولي لبذور العنب و الشاي الأخضر على التغيرات الكروموسومية و معامل الانقسام الخيطي في الفئران المختبرية: Study the effect different concentrations of active substances derived from plants on chromosome aberrations and Mitotic index in laboratory mice - علوان أقبال فاضل (University of Thi-Qar Journal of Science, 2014)
Antioxidants studied extensively for its ability to protect the cells of living organisms from oxidative damage, and confirmed a lot of researchers mention of grape seed and green tea as effective against the oxidation process. Was obtained extracts alcoholic plants grape seed and green tea, for the purpose of formula extracts of medicinal plants and contain components of this formula 125mg of extract alcohol to grape seed and 125mg of extract alcohol of green tea with the addition of a number of vitamins (A,C,E).Having examined the toxic effects of three differentconcentrations of formula (50, 100, 200 mg) on laboratory mice by oral dosage within a month of the experiment . The results indicated that there were no significant differences at the level of ( p<0.05) for concentrations of alcoholic extracts of grape seed and green tea to induce chromosomal aberrations and mitotic index , mention the results on any effect toxicity dose used compared to control animals .